Improvement of management processes in internal affairs bodies. - Prokopiv, Bohdan (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
To improve the management processes in the internal affairs bodies, the accumulation of information on advanced methods and methods of management, and the study of the experience of the domestic and foreign, modern and past, and the introduction of scientific organization of labor, understanding that without technical means of processing information, it is impossible to make informed solutions and effective management.                                                                 To date, in fact, new divisions of law-enforcement bodies have been established, acting on the basis of the laws of a sovereign state, the staff of law-enforcement bodies has been updated, which has taken place over the past four years, new complex tasks that the interior affairs bodies and international cooperation must solve; need to improve work with personnel; the embodiment of the scientific foundations of the organization of labor in the practical activities of the organs of internal affairs-makes it necessary to study the problems of theory, practice, and ways of improving management in the organs of internal affairs.